1994
DOI: 10.1002/ajim.4700260314
|View full text |Cite
|
Sign up to set email alerts
|

Organization and classification of work history data in industry‐wide studies: An application to the electric power industry

Abstract: Industry-based cohort studies require systems for organizing work history data. Although the ultimate goal may be to assess the hazards of specific exposures, classification of the job titles that comprise work histories serves an important descriptive purpose in itself and is often necessary before exposure data can be obtained. A system we have created for organizing jobs in a study of 135,000 workers at five electric power companies highlights conceptual and practical issues in managing work history data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Details of the sampling design and field methods of the magnetic field exposure survey have been described elsewhere (1 8), as have the classification and organization of the work history data from the cohort (19). A brief description of the survey is provided.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the sampling design and field methods of the magnetic field exposure survey have been described elsewhere (1 8), as have the classification and organization of the work history data from the cohort (19). A brief description of the survey is provided.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a large survey of occupational exposure to 60-Hz magnetic fields among randomly selected worlcers in 28 job categories in five electric utility companies (18)(19)(20). In relation to earlier assessments of occupational magnetic field exposure, this study has several design advantages that facilitate the examination of exposure variability.…”
mentioning
confidence: 99%
“…24,25 Exposure to EMFs was estimated by an assessment of exposure to magnetic fields, focusing on the time-weighted average, as described in detail elsewhere and briefly summarized here. 19,[26][27][28] Complete work histories were abstracted and computerized. To consolidate thousands of job titles at the 5 participating companies, 28 occupational categories were constructed based on work activities, responsibilities, and exposure potential 26 to define the rows of a job exposure matrix.…”
mentioning
confidence: 99%
“…19,[26][27][28] Complete work histories were abstracted and computerized. To consolidate thousands of job titles at the 5 participating companies, 28 occupational categories were constructed based on work activities, responsibilities, and exposure potential 26 to define the rows of a job exposure matrix. Within the occupational categories, 1,060 distinct job titles were monitored.…”
mentioning
confidence: 99%
“…An exception to this lack of information was a study of electrical workers (37), in which a detailed description was provided as to how the investigators developed their exposure groups. We recommend that the exposure estimation class used in studies be identified and documented in a similar manner.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%